Penyuluhan Tentang Bahaya Perundungan Melalui Pendekatan Olahraga Permainan di Sekolah Dasar - Andi Temmasonge; Alif Aryadi Hardi; Andi Nurul Ihsan; Rahmat Ilahi; Muhammad Harliawan (Universitas PGRI Palembang, 2024)
The problem of bullying is a fairly complex problem for students that must be anticipated by parents and educators. The rampant acts of bullying result in physical and even psychological disturbances to the victim, which is carried out by mocking, insulting, threatening, isolating, and even abusing the victim so that the victim will feel depressed. Schools, which are supposed to be places for play and character development, have turned into terrible places for victims of bullying. Ironically, cases of bullying that occur in children are increasing from year to year, which requires serious attention so that it can be minimized, especially in elementary schools as a place for character formation from the start. In the school environment there are still many cases of bullying that occur and are considered trivial by the bullies. The results of this service show a decrease in bullying incidents after the counseling, although previously there were often cases of exclusion, bullying and the use of negative nicknames according to the results of interviews with students, teachers and parents. These findings emphasize the importance of adequate education and understanding about bullying from an early age so that students can recognize and develop attitudes against violence.